Sexual practices and condom use among a sample of Northern and Indigenous adolescents in Northern Canada: cross-sectional survey results. Issue 2 (27th December 2018) - Logie, Carmen H; Lys, Candice L; Fujioka, Jamie; MacNeill, Nancy; Mackay, Kayley; Yasseen III, Abdool S
Abstract : Background: Sexually transmitted infections (STI) prevention in the Northwest Territories (NWT), Canada is an urgent concern as STI prevalence is seven-fold the national average. The study objective was to explore factors associated with sexual activity and condom use among adolescents in the NWT. Methods: We conducted a cross-sectional survey with youth aged 13–18-years-old in 17 NWT communities. We use Poisson regression models with a robust sandwich error variance to estimate adjusted relative risks estimates of the likelihood of experiencing the primary outcomes of sexual activity (vaginal/anal/oral sex) and consistent condom use (oral/anal sex) in the past 3 months by gender. Results: Participants (n=607; mean age: 14.2 years; SD: 1.5) included adolescent cisgender girls (n=302; 49.5%), cisgender boys (n=298; 48.9%) and transgender persons (n=7; 1.2%). Most identified as Indigenous (n=444; 73.1%) and 14.0% (n=85) as lesbian, gay, bisexual or queer sexuality (LGBQ+). Among sexually active individuals (n=115), less than half (n=54; 47.0%) reported past 3 month consistent condom use. In adjusted analyses among girls, sexual activity was associated with age, STI knowledge, and alcohol/drug use; LGBQ+ identity and alcohol/drug use were associated with reduced likelihood of condom use. Among boys, sexual activity was associated with age and alcohol/drug use; LGBQ+ identity was associated with increased likelihood of condom use. Conclusions: Findings demonstrate sexual activity among adolescents in the NWT varies by gender, age, and alcohol/drug use. Consistent condom utilisation was low, particularly for those using alcohol/drugs. Gender-tailored STI prevention strategies with Northern adolescents should address alcohol/drug use and build protective factors.